Drug–drug interaction and initial dosage optimization of aripiprazole in patients with schizophrenia based on population pharmacokinetics - Zhang, Cun; Jiang, Lei; Hu, Ke; Zhang, Yi-Jia; Han, Jing; Chen, Jin; Bulubu,; Dong, Boling; Shi, Hao-Zhe; He, Su-Mei; Yu, Ting-Ting; Chen, Xiao; et al. (Frontiers in Psychiatry, 2024)
Background: The present study was to investigate the drug-drug interaction and initial dosage optimization of aripiprazole in schizophrenia patients based on population pharmacokinetics. Research Design and Methods: A total of 119 schizophrenia patients treated by aripiprazole were collected to build aripiprazole population pharmacokinetic model using nonlinear mixed effect. Results: Weight and concomitant medication of fluoxetine influenced aripiprazole clearance. Under the same weight, the aripiprazole clearance rates were 0.714:1 in patients with or without fluoxetine, respectively. In addition, without fluoxetine, for once-daily aripiprazole regimen, the dosages of 0.3, and 0.2 mg/kg/day were recommended for patients with schizophrenia with weights of 40-95, and 95-120 kg, respectively; for twice-daily aripiprazole regimen, the dosage of 0.3 mg/kg/day was recommended for patients with schizophrenia with weights of 40-120 kg. With fluoxetine, for once-daily aripiprazole regimen, the dosage of 0.2 mg/kg/day was recommended for patients with schizophrenia with weights of 40-120 kg; for twice-daily aripiprazole regimen, the dosages of 0.3, and 0.2 mg/kg/day were recommended for patients with schizophrenia with weights of 40-60, and 60-120 kg, respectively. Conclusion: It was the first time to investigate the effects of fluoxetine on aripiprazole via drug-drug interaction and recommend the optimal aripiprazole initial dosage in patients with schizophrenia.